Crop genetic diversity in the field and on the farm: principles and applications in research practices - Jarvis, Devra I.; Hodgkin, T.; Brown, A.H.D.; Tuxill, J.; López Noriega, Isabel; Smale, Melinda; Sthapit, B.R. (Yale University Press, 2016)
Based on twenty years of global research, this is the first comprehensive reference on crop genetic diversity as it is maintained on farmland around the world. Showcasing the findings of seven experts representing the fields of ecology, crop breeding, genetics, anthropology, economics, and policy, this invaluable resource places farmer-managed crop biodiversity squarely in the center of the science needed to feed the world and restore health to our productive landscapes. It will prove to be an essential tool in the training of agricultural and environmental scientists seeking the solutions necessary to ensure healthy, resilient ecosystems for future generations.